TREM2 rare variant p.R47H is not associated with Parkinson's disease. (February 2016) - Mengel, David; Thelen, Mathias; Balzer-Geldsetzer, Monika; Söling, Charlotte; Bach, Jan-Philipp; Schaeffer, Eva; Herold, Christine; Becker, Tim; Liepelt, Inga; Becker, Julian; Riedel-Heller, Steffi; Scherer, Martin; et al.
Abstract: Variant p.R47H of triggering receptor expressed on myeloid cells 2 ( TREM2) has been associated with Parkinson's disease (PD). We screened this TREM2 -variant in 821 PD patients including 261 demented PD patients (PDD) and in healthy controls (n = 919). Neither the entire PD nor the small PDD sample was associated with p.R47H.